2002
DOI: 10.1136/gut.51.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparative study of spiral computer tomography and magnetic resonance imaging for detection of hepatocellular carcinoma

Abstract: Background: Hepatocellular carcinoma (HCC) is often detected at a relatively late stage when tumour size prohibits curative surgery. Screening to detect HCC at an early stage is performed for patients at risk. Aim: The aim of this study was to compare prospectively the diagnostic accuracy and classification for management of the two state of the art secondline imaging techniques: triphasic spiral computer tomography (CT) and super paramagnetic iron oxide (SPIO) enhanced magnetic resonance imaging (MRI). Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 4 publications
1
21
0
1
Order By: Relevance
“…However, when preoperative liver imaging is compared with pathological findings, the sensitivity of Lipiodol CT is only 53 per cent 46 , and up to 10 per cent of patients who undergo liver transplantation for chronic liver disease will have incidental tumours in the explanted liver 4,47 . Recent studies have suggested that MRI is better than CT in detecting HCC (sensitivities of 76 versus 61 per cent), particularly for tumours 1-2 cm in diameter 46,48,49 . However, there is no effective method for detecting tumours less than 1 cm in diameter; MRI fails to identify these lesions in approximately two-thirds of patients 46 .…”
Section: Assessment Before Transplantationmentioning
confidence: 98%
See 1 more Smart Citation
“…However, when preoperative liver imaging is compared with pathological findings, the sensitivity of Lipiodol CT is only 53 per cent 46 , and up to 10 per cent of patients who undergo liver transplantation for chronic liver disease will have incidental tumours in the explanted liver 4,47 . Recent studies have suggested that MRI is better than CT in detecting HCC (sensitivities of 76 versus 61 per cent), particularly for tumours 1-2 cm in diameter 46,48,49 . However, there is no effective method for detecting tumours less than 1 cm in diameter; MRI fails to identify these lesions in approximately two-thirds of patients 46 .…”
Section: Assessment Before Transplantationmentioning
confidence: 98%
“…A recent study suggested that by excluding patients with poorly differentiated tumours using routine tumour biopsy, it may be possible to reduce recurrence after transplantation to less than 10 per cent 48 . In this series, there were no biopsy-related complications and 5-year actuarial and recurrence-free survival was 75 and 92 per cent respectively 48 . Although this is the only study to examine the role of tumour biopsy in the transplant setting, the initial results are encouraging.…”
Section: Tumour Staging Systemsmentioning
confidence: 99%
“…By contrast, the MC, UCSF and Onaca et al (42) proposal rely on factors (tu- ITT = intention to treat ¥ = patient survival (PS) ² = recurrence free rate (RR) Staging refers to the method used for tumor staging. P = pretransplant radiology; R = explant tumor pathology; NA = not available mor size and number) that can be determined by preoperative imaging, however, such criteria must consider the limitations of imaging studies (7,23,48,55,56,59,60) . The continued improvement in imaging techniques may decrease the gap between imaging and pathology of HCC, although some understanding will certainly continue to exist (53) .…”
Section: Discussionmentioning
confidence: 99%
“…In doubtful cases, nuclear crowding is ascertained by semiquantitative analysis showing an increased cellularity, which should be at least twice as that seen in the surroundings. 15 Unpaired arteries (Fig. 1M): intraparenchymal arterioles unassociated to portal tracts.…”
Section: Map-likementioning
confidence: 99%
“…1 Major progresses in their identification and understanding were provided by imaging evaluation in vivo, making possible the sampling of small early lesions (0.5-2 cm) and to follow their natural history. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Most of the advances in the field have been achieved through the systematic macro-and microscopical examination of native transplanted end-stage cirrhotic livers; however, there is a substantial lack of information on the morphological features of ultrasound (US)-detected hepatocellular nodules on liver biopsies. Indeed, the differential diagnosis of these lesions, while relatively easy on surgical specimens, is a challenging one on small liver biopsies, even for experienced hepatopathologists.…”
mentioning
confidence: 99%